Tuberculosis espinal: opciones de tratamiento mas allá de las guías clínicas - Inês Esteves Cruz; João Torres (Sociedade Galega de Medicina Interna, 2021)
Spinal tuberculosis, a presentation of extrapulmonary tuberculosis, usually presents with chronic back pain or deformity. The diagnosis is often delayed due to the insidious and nonspecific nature of the initial symptoms. The thoracic spine is more commonly affected, but it can affect other segments or be multisegmental. The site and extent of the lesion will determine the resulting neurological deficits which can lead to significant morbidity and functional impairment. Combination chemotherapy for 6 months is recommended, but some experts may recommend therapy for 9 to 12 months depending on the circumstances. Adjunct corticotherapy and surgery are also options in specific cases. Further studies will be needed in order to better understand the role of these therapies in severe tuberculosis, and in particular spinal tuberculosis.